Some Reflections on Artificial Insemination and Extrauterine Fertilization - Cárdenas Quirós, Carlos (1988)
The text analyzes advances in artificial insemination and in vitro fertilization techniques, exploring their legal, ethical and social implications. The author recognizes that these technologies represent a significant solution to infertility, but raise challenges related to the nature of procreation, filiation and human dignity. He also acknowledges that homologous techniques, which use gametes from spouses, generate less ethical controversy, while heterologous techniques, which use gametes from third parties, are criticized for potentially affecting the marital unit and the rights of the child. In addition, controversial issues such as the use of post-mortem gametes and the creation of embryos for experimental purposes are addressed. Finally, the author emphasizes the importance of adequate legal regulation to avoid possible abuses, highlighting international examples, such as the legal frameworks of Great Britain and Australia, which seek to balance scientific advances with respect for ethical and social principles.